2018
DOI: 10.2217/bmm-2018-0100
|View full text |Cite
|
Sign up to set email alerts
|

The Association Among Biomarkers of Renal and Heart Function in Patients With Heart Failure: the Role of NGAL

Abstract: Aim: The NGAL is a biomarker of renal injury associated with the progression of heart failure (HF). We examine the association of NGAL with galectin-3 in patients with chronic HF. Methods: We consecutively enrolled 115 subjects with stable ischemic HF of reduced ejection fraction. Serum levels of galectin-3, b-type natriuretic peptide and NGAL were measured. Results: NGAL levels were positively correlated with galectin-3 (rho = 0.26; p = 0.04) and b-type natriuretic peptide levels (rho = 0.30; p = 0.005) and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…By MTT proliferation, wound healing and transwell assays, it was found that overexpression NGAL in NPC cells inhibited the proliferation and migration of NPC cells. These results suggest NGAL plays a cancer suppressor role in NPC, which is different from most solid tumors (12,15). Overexpression of NGAL also induces moderate apoptosis and further study demonstrated that overexpression of NGAL inhibited the caspase family activation.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…By MTT proliferation, wound healing and transwell assays, it was found that overexpression NGAL in NPC cells inhibited the proliferation and migration of NPC cells. These results suggest NGAL plays a cancer suppressor role in NPC, which is different from most solid tumors (12,15). Overexpression of NGAL also induces moderate apoptosis and further study demonstrated that overexpression of NGAL inhibited the caspase family activation.…”
Section: Discussionmentioning
confidence: 83%
“…NGAL, also known as lipocalin-2 (lcn2), is a 24 kDa glycoprotein in humans encoded by the lcn2 gene located at position 3P11 of chromosome 9. In recent years, it has become a biomarker for some benign and malignant diseases (13)(14)(15)(16)(17). The effect of NGAL in carcinogenesis is dependent on cancer type.…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophil gelatinase-associated lipocalin (NGAL), also known as lipocalin-2 protein, is a 25-kDa protein involved in the host defense against some gram-negative bacteria through binding with iron-loaded bacterial siderophores, which limits the availability of this essential nutrient to bacteria, leading to inhibition of their growth and pathogenicity [5]. NGAL levels have been used to reflect tissue damage, particularly in the kidney, and more recently for cardiovascular disease manifestations, including hypertensive cardiac hypertrophy [6], coronary artery disease [7], and acute heart failure [8]. Oikonomou et al reported a positive correlation between NGAL and myocardial fibrosis and remodeling in heart failure patients [8].…”
Section: Introductionmentioning
confidence: 99%
“…NGAL levels have been used to reflect tissue damage, particularly in the kidney, and more recently for cardiovascular disease manifestations, including hypertensive cardiac hypertrophy [6], coronary artery disease [7], and acute heart failure [8]. Oikonomou et al reported a positive correlation between NGAL and myocardial fibrosis and remodeling in heart failure patients [8]. Shalenkova et al found that NGAL may be used as a marker for severity of cardiovascular conditions and heart remodeling in patients after exacerbation of ischemic heart disease [9].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with CHF, an increase in all-cause mortality and hospitalization have been associated with NGAL activation in cardiomyocytes and an increase in its level [5].…”
mentioning
confidence: 99%